Youth Participation, Media Literacy and Social Justice - Hauge, Chelsey; Shepherd, Tamara; Garcia, Antero; Cucinelli, Giuliana; Bryson, Mary (AoIR Selected Papers of Internet Research, 2013)
As digital media have become increasingly ubiquitous, educational institutions, non-for-profit-organizations, and governmental institutions have responded by initiating various programs and research activities that indicate a concern over how, and to what social and political ends, youth engage with media. Within mediated spaces, participatory language has been used to celebrate young people’s engagement in social networks and online environments, including platforms like YouTube and Facebook, and other digital technologies such as mobile apps and video games (Ito et al., 2009; Jenkins, 2006). There is particular interest in understanding how participation in mediated environments fosters civic engagement, knowledge, and civic participation (Rheingold, 2008). Yet many scholars have problematized the possibility that participation in digital media might foster new forms of civic engagement or political action for youth, since digital spaces often replicate existing structures of exclusivity and inequity (Hindman, 2008; Davis, 2009). This panel explores the tensions around participation in digital environments, in order to consider what it might mean for young people to learn how to practice citizenship through media literacy. Given the promise around the possibility that digital citizenship might relate to “social justice” as a kind of resistance against neoliberal appropriation, we attempt here to understand how participation in media spaces is negotiated by youth in relation to political practices.Methodologically, this panel orients itself around critical approaches to pedagogy, where ethnographic and discursive methods are used in the service of highlighting the structures of power that shape young people’s everyday modes of media participation. We frame this participation as a kind of media or digital literacy, while attempting to de-stabilize the dominant framings of participation as necessarily in line with social justice or any other particular version of politics. By asking what participation means for young people engaging in a variety of digital practices, we aim to contribute to theorizations of digital citizenship as the way in which youth enter civic life through mediated environments (Papacharissi, 2010).This panel addresses the following questions:• How are mediated environments taken up as a tool for social justice and civic engagement, and what tensions surface in doing so with international groups of youth?• How might we theorize youth political participation and democratic practice? What are the political tensions brought about when youth participate in mediated spaces, especially as related to citizenship, democratic practice, and difference?• How is the excitement and hope surrounding digital media engagement taken up in governmental and non-profit initiatives, and how do those initiatives address and construct youth in media spaces?The first paper, “Hope, youth media, and democratic practice,” addresses the ways in which youth enact democratic practice as they participate in media production programming, conceptualizing of democratic engagement through Rancière’s work on radical democracy to theorize how youth make their stories visible from within the colonial context of community development practice. Second, the paper “Social relations, geographical constructions of youth cultures and urban youth media production ecologies in Canada” examines the spatial ecologies of youth media production organizations, and how their evolution reflect class based tensions as they play out in programming that attempts to expand social capital for marginalized youth. Third, the paper “Geocaching and Civic Engagement in Simultaneous Online and Offline Environments” discusses the affordances of geo-caching for civic engagement in the everyday practice of youth culture. The fourth paper, “Rethinking participation as engagement in Canada’s Digital Economy Strategy,” explores the implications of the Canadian Digital Economy Strategy for digital citizenship, analyzing how its policy language constructs youth as digital citizens by conflating participation in digital spaces with civic engagement. Together, these four papers illustrate the far-reaching implications of digital citizenship for young people’s engagement with social justice as they negotiate what it means to participate in mediated spaces.ReferencesDavis, A. (2009). New media and fat democracy: The paradox of online participation. New Media & Society, 11(8), 1-20.Hindman, M. (2008). The myth of digital democracy. Princeton: Princeton University Press.Ito, M., Baumer, S., Bittanti, M., boyd, d., Cody, R., Herr-Stephenson, B., & Horst, H. (2009). Hanging out, messing around, and geeking out: Kids living and learning with new media. Cambridge: The MIT Press.Jenkins, H. (2006). Fans, bloggers, and gamers: Exploring participatory culture. New York: New York University Press.Papacharissi, Z. (2010). A Private Sphere: Democracy in a Digital Age. Cambridge, UK: Polity.Rhinegold, H. (2008). Using participatory media and public voice to encourage civic engagement. In W.L. Bennett (Ed.), Civic life online: Learning how digital media can engage youth (pp. 97-118). Cambridge: The MIT Press.